The impact of sharia financial literacy levels on public understanding in conducting transactions at sharia banks in Semarang City - Syakur, Riza Rizki Faozan; Arifin, Johan; Turmidi, A (Jurnal Bisnis Mahasiswa, 2025)
Understanding financial literacy is increasingly vital for effective financial management within communities, helping to prevent financial issues. ‘This study explores the impact of sharia financial literacy’ on the Semarang community's transaction behaviors at Bank Syariah Indonesia, using a quantitative research method. The population includes the Semarang community, with proportional random sampling employed for data collection. Results indicate that Basic Financial Knowledge significantly influences savings interest at Bank Syariah Indonesia (t = 4.469, p < 0.05). Additionally, the variables of Savings and Financing (t = 3.071, p = 0.028) and Investment (t = 4.169, p = 0.003) also show significant positive effects.